1982
DOI: 10.1073/pnas.79.3.835
|View full text |Cite
|
Sign up to set email alerts
|

Interferon inhibits Sendai virus-induced cell fusion: an effect on cell membrane fluidity.

Abstract: Interferon can affect several cellular functions, in addition to its antiviral activity. We report here that pretreatment of human cells with homologous interferon significantly inhibits cell fusion induced by Sendai virus and that this refractory state is accompanied by a decrease in cell plasma membrane fluidity. Multinucleate cell formation induced by 13-propiolactone-inactivated Sendai virus in human fibroblast cells (a system in which fusion results from an interaction ofthe viral glycoprotein with the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Inhibition was maximum at 24 h after treatment with 1,000 U of interferon per ml and was dose dependent and reversible with time. Pinocytosis was inhibited when human and chicken embryo cells were treated with homologous, but not heterologous, interferons.In addition to inhibiting viral replication, interferon treatment of cells produces a variety of effects on the plasma membrane (2,3,7,9,12,15) 91:238a, 1981) reported that interferon treatment of thioglycollate-elicited mouse peritoneal macrophages caused a marked change in the distribution of microtubules and 10-nm filaments in a major fraction of the cells; this alteration was correlated with an inhibition of pinocytosis. The results reported here describe some details of the inhibition of pinocytosis in cells treated with interferon.…”
mentioning
confidence: 99%
“…Inhibition was maximum at 24 h after treatment with 1,000 U of interferon per ml and was dose dependent and reversible with time. Pinocytosis was inhibited when human and chicken embryo cells were treated with homologous, but not heterologous, interferons.In addition to inhibiting viral replication, interferon treatment of cells produces a variety of effects on the plasma membrane (2,3,7,9,12,15) 91:238a, 1981) reported that interferon treatment of thioglycollate-elicited mouse peritoneal macrophages caused a marked change in the distribution of microtubules and 10-nm filaments in a major fraction of the cells; this alteration was correlated with an inhibition of pinocytosis. The results reported here describe some details of the inhibition of pinocytosis in cells treated with interferon.…”
mentioning
confidence: 99%
“…Both studies confirmed broad antiviral activity of 25HC in vitro against different classes of lipid-enveloped RNA and DNA viruses. This was subsequently reaffirmed by several independent studies (Arita et al 2013;Chen et al 2014;Mboko et al 2014), and the antiviral activity was additionally extended to nonenveloped viruses (Civra et al 2014). Table 1 summarizes the viruses whose susceptibility to 25HC's antiviral effects has been validated.…”
Section: Hc: Broad Antiviral Lipid Effectormentioning
confidence: 57%
“…IFN inhibits the production of viral glycoproteins, thus affecting the membrane-associated steps of viral replication (Chatterjee et al, 1985). Alternatively, IFN may change the fluidity of membranes and thereby disrupt viral morphogenesis (Chatterjee et al, 1982;Pfeffer et al, 1981 ;Wang et al, 1981).…”
Section: Discussionmentioning
confidence: 99%